Influence of a One-Time Web-Based Provider Intervention on Patient-Reported Outcomes After the Well-Child Visit: A Feasibility Study - Chad M. Coleman; Gwen L. Alexander; Charles Barone; Andrew S. Bossick; Zeinab Kassem; Mei Lu; Yueren Zhou; Andrea E. Cassidy-Bushrow (Journal of Patient-Centered Research and Reviews, 2021)
Purpose: Patient-centered care promotes positive health outcomes in pediatrics. We created a provider-focused intervention and implemented it in a pragmatic clustered randomized controlled trial to improve health-related quality of life (HRQOL) among pediatric patients.